PEMANFAATAN APLIKASI KINEMASTER SEBAGAI PEMBUATAN MEDIA PEMBELAJARAN TEMATIK DI SD IT AL-BINA 01 KOTO BARU - Nadiya Elsa Putri; Adam Mudinillah (Jurnal Ilmiah Ibtida: Jurnal Prodi PGMI STIT Pemalang, 2021)
Thematic learning at SD IT Al-Bina 01 Koto Baru during the covid-19 pandemic has decreased in terms of quality and in the learning process. After researching this happens because of the ineffectiveness of the learning process and the less optimal of teachers in conveying information related to learning materials. Where we know that usually during face-to-face learning, students are more focused and more effective in the teaching and learning process with directives and delivery from the teacher. Compared to current online learning, the use of smartphones as a communication tool in online learning is considered ineffective and efficient. Because as we know that there are many other non-educational applications on smartphones that can interfere with students' concentration and focus. This is certainly closely related to the learning system and the use of inappropriate learning media. This study uses a descriptive research method, using data analysis of the comparison of student scores in the last three years. After the operation of this thematic learning video media to students, it turned out that the survey proved that with these learning media videos, the quality of student learning outcomes at SD IT Al-Bina 01 has increased.